The Entrepreneurial Society (Springer Nature, 2021)
This open access book is an outcome of the EU’s Horizon 2020 project ‘Financial and Institutional Reforms for an Entrepreneurial Society’ (FIRES). Building on historical, economic and legal analysis, and combining methods and data across disciplines, the authors provide policymakers, stakeholders and scholars with valuable new tools for assessing and improving Europe’s entrepreneurial ecosystems. Then experts from Germany, Italy and the United Kingdom discuss tailored strategies for introducing entrepreneurial policy reforms in their respective countries.